Motives, identity, and behaviors: a case study of the experiences of a trans woman convicted of sexual crimes - Neyenhaus, Janna M. (Criminal justice studies, 2025)
There is research regarding the experiences of transgendered persons and for those who have been convicted of sexual crimes. However, there are limited studies focusing on the specific population of transgender individuals who have committed sexual crimes and their experiences within the criminal justice system. This case study examined the experiences of a transgender person, who also committed a sex crime. There were a variety of factors that affected her experiences and mental health, including her personal views on gender identity, correctional officers and prison administration, access to medical care/hormone therapy, rehabilitation programs, other incarcerated persons within the prisons, and the work release program. We discuss how the double labeling of sex criminal and transgender person, and the stigmas attached to such, affect identity and behavior. Future research and directions are also discussed.